Alkali-free glass plate
By strictly controlling the glass characteristics of alkali-free glass plates, the thermal dimensional stability problems of large-scale, thinner and high-resolution are solved, and the effects of excellent productivity and cost reduction are achieved.
Patent Information
- Application Number
- CN202180036263.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-18
- Filing Date
- 2021-06-15
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-06-15
AI Technical Summary
The existing alkali-free glass plates are difficult to maintain high-resolution thermal dimensional stability while being larger and thinner, and are costly and easily deflective, affecting production efficiency.
By strictly controlling the glass characteristics of alkali-free glass plates, the content of Li2O+Na2O+K2O is ensured to be 0-0.5 mol%, Young's modulus reaches more than 80GPa, the strain point reaches more than 700℃, and the liquid phase temperature is less than 1350℃.
The alkali-free glass plate with excellent productivity and sufficiently improved Young's modulus and strain point is achieved, which reduces the deflection amount and cost, and meets the requirements of large-scale, thinner and high-resolution.
Smart Images

Figure BDA0003949672840000111
Abstract
Description
Technical Field
[0001] The present invention relates to an alkali-free glass plate, and in particular to an alkali-free glass plate suitable for an organic EL display. Background Art
[0002] Electronic devices such as organic EL displays are used for applications such as flexible devices and mobile phone displays because they are thin, excellent in video display, and have low power consumption.
[0003] Glass plates are widely used as substrates for organic EL displays. The following properties are mainly required for glass plates for this purpose.
[0004] (1) In order to prevent alkali ions from diffusing into the semiconductor material formed into a film during the heat treatment process, it is required to contain almost no alkali metal oxides, that is, to be alkali-free glass (the content of alkali oxides in the glass composition is 0.5 mol% or less);
[0005] (2) In order to make the glass sheet cheaper, excellent productivity, especially excellent meltability and resistance to devitrification are required;
[0006] (3) In the LTPS (low temperature polysilicon) process and the oxide TFT process, a high strain point is required to reduce the thermal shrinkage of the glass plate.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2012-106919 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] In addition, organic EL devices are widely used in organic EL TVs. There is a strong demand for large-scale and thin-type organic EL TVs, and the demand for high-resolution displays such as 8K is increasing. Therefore, for glass plates for these purposes, it is required to be large-scale, thin and have thermal dimensional stability that can meet the requirements of high resolution. Moreover, in order to reduce the price difference with liquid crystal displays, further low cost is required, and low cost is also required for glass plates. However, if the glass plate is large-scale and thin, it becomes easy to bend, and the manufacturing cost rises.
[0012] The glass plates formed by glass manufacturers go through the processes of cutting, annealing, inspection, and cleaning, but during these processes, the glass plates are put into a box formed with multiple shelves and carried out. The box usually places the opposite sides of the glass plates on the shelves formed on the left and right inner sides and can hold them in the horizontal direction, but the large and thin glass plates have a large deflection amount, so when the glass plates are put into the box, part of the glass plates will contact the box and break, or when they are carried out, they are easily shaken and become unstable. Electronic device manufacturers also use boxes of this shape, so the same problem occurs. In order to solve this problem, it is effective to increase the Young's modulus of the glass plate and reduce the deflection amount.
[0013] Furthermore, as described above, in the LTPS and oxide TFT processes for obtaining high-resolution displays, it is necessary to increase the strain point of a large glass plate in order to reduce thermal shrinkage of the large glass plate.
[0014] However, if the Young's modulus and strain point of the glass sheet are to be increased, the balance of the glass composition will be broken, the productivity will be easily reduced, and in particular, the devitrification resistance will be significantly reduced. In addition, the melting property will be easily reduced or the forming temperature of the glass will be easily increased, and the life of the formed body will be easily shortened. As a result, the original plate cost of the glass sheet will rise.
[0015] Therefore, the present invention has been made in view of the above circumstances, and a technical object of the present invention is to provide an alkali-free glass plate having excellent productivity and sufficiently high strain point and Young's modulus.
[0016] Means used to solve problems
[0017] As a result of repeated various experiments, the inventors discovered that the above-mentioned technical problems can be solved by strictly controlling the glass properties of the alkali-free glass plate, and proposed the present invention. That is, the alkali-free glass plate of the present invention is characterized in that the content of Li2O+Na2O+K2O in the glass composition is 0-0.5 mol%, the Young's modulus is above 80 GPa, the strain point is above 700°C, and the liquidus temperature is below 1350°C. Here, "Li2O+Na2O+K2O" refers to the total amount of Li2O, Na2O and K2O. "Young's modulus" refers to the value measured by the bending resonance method. It should be noted that 1 GPa is equivalent to approximately 101.9 Kgf / mm 2 "Strain point" refers to the value measured based on the method of ASTM C336. "Liquidus temperature" refers to the temperature at which crystals are precipitated after glass powder that passes through a standard sieve of 30 mesh (500 μm) and remains in a 50 mesh (300 μm) sieve is placed in a platinum boat and kept in a temperature gradient furnace for 24 hours.
[0018] The alkali-free glass plate of the present invention is characterized in that, as a glass composition, it contains, in mol%, 64 to 71% of SiO2, 12 to 17% of Al2O3, 0 to 5% of B2O3, 0 to 0.5% of Li2O+Na2O+K2O, 5 to 9% of MgO, 2 to 10% of CaO, 0 to 7% of SrO, more than 1% and less than 7% of BaO, 14 to 20% of MgO+CaO+SrO+BaO, a mol ratio of Al2O3 / BaO of 1.8 to 10, a mol ratio of B2O3 / (MgO+CaO+SrO+BaO) of 0 to 0.2, a mol ratio of (B2O3+MgO) / SiO2 of 0.1 to 0.2, and a mol ratio of B2O3 / MgO of 0 to 0.5. Here, "MgO+CaO+SrO+BaO" means the total amount of MgO, CaO, SrO and BaO. “Al2O3 / BaO” refers to the value obtained by dividing the content of Al2O3 by the content of BaO. “B2O3 / (MgO+CaO+SrO+BaO)” refers to the value obtained by dividing the content of B2O3 by the total amount of MgO, CaO, SrO and BaO. “(B2O3+MgO) / SiO2” refers to the value obtained by dividing the total amount of B2O3 and MgO by the content of SiO2. “B2O3 / MgO” refers to the value obtained by dividing the content of B2O3 by the content of MgO.
[0019] In addition, the alkali-free glass plate of the present invention preferably contains substantially no As2O3 and no Sb2O3. Here, "substantially contains no As2O3 and no Sb2O3" means that the contents of As2O3 and Sb2O3 in the glass composition are each less than 0.05%.
[0020] Moreover, the alkali-free glass plate of the present invention preferably further contains SnO2 in an amount of 0.001 to 1 mol%.
[0021] Moreover, the alkali-free glass plate of the present invention preferably has a strain point of 710° C. or higher.
[0022] Moreover, the alkali-free glass plate of the present invention preferably has a Young's modulus higher than 81 GPa.
[0023] The alkali-free glass plate of the present invention preferably has an average thermal expansion coefficient of 30×10 -7 ~50×10 -7 Here, the "average thermal expansion coefficient in a temperature range of 30 to 380° C." can be measured using a dilatometer.
[0024] In addition, the alkali-free glass plate of the present invention preferably has a liquidus viscosity of 10 4.0 Here, the "liquid phase viscosity" refers to the viscosity of the glass at the liquid phase temperature, and can be measured by a platinum ball pulling method.
[0025] Furthermore, the alkali-free glass plate of the present invention is preferably used for an organic EL device. DETAILED DESCRIPTION
[0026] The alkali-free glass plate of the present invention is characterized in that, as a glass composition, it contains, in mol%, 64 to 71% of SiO2, 12 to 17% of Al2O3, 0 to 5% of B2O3, 0 to 0.5% of Li2O+Na2O+K2O, 5 to 9% of MgO, 2 to 10% of CaO, 0 to 7% of SrO, more than 1% and less than 7% of BaO, 14 to 20% of MgO+CaO+SrO+BaO, a mol ratio of Al2O3 / BaO of 1.8 to 10, a mol ratio of B2O3 / (MgO+CaO+SrO+BaO) of 0 to 0.2, a mol ratio of (B2O3+MgO) / SiO2 of 0.1 to 0.2, and a mol ratio of B2O3 / MgO of 0 to 0.5. The reasons for limiting the contents of the components as described above are shown below. In addition, in the description of the content of each component, the expression of % means mol % unless otherwise specified.
[0027] SiO2 is a component that forms the skeleton of glass. If the content of SiO2 is too little, the thermal expansion coefficient becomes high and the density increases. Therefore, the lower limit of SiO2 is preferably 64%, more preferably 64.2%, more preferably 64.4%, more preferably 64.6%, more preferably 64.8%, more preferably 65%, and most preferably 65.2%. On the other hand, if the content of SiO2 is too much, the Young's modulus decreases, and then the high-temperature viscosity becomes high, the heat required during melting becomes more, the melting cost rises, and the defect caused by the melting residue of the SiO2 raw material occurs, which may become the reason for the reduction of the yield rate. In addition, devitrified crystals such as cristobalite become easy to precipitate, and the liquidus viscosity is easy to reduce. Therefore, the upper limit of SiO2 is preferably 71%, more preferably 70.8%, more preferably 70.6%, more preferably 71.4%, more preferably 70.2%, more preferably 70%, and most preferably 69.8%.
[0028] Al2O3 is a component that forms the skeleton of glass, a component that increases Young's modulus, and a component that increases strain point. If the content of Al2O3 is too little, Young's modulus is easily reduced, and the strain point is easily reduced. Therefore, the lower limit of Al2O3 is preferably 12%, more preferably more than 12%, more preferably 12.1%, more preferably 12.2%, more preferably 12.5%, more preferably 12.6%, more preferably 12.8%, and most preferably 13%. On the other hand, if the content of Al2O3 is too much, devitrified crystals such as mullite become easy to precipitate, and liquidus viscosity is easy to reduce. Therefore, the upper limit of Al2O3 is preferably 17%, more preferably 16.8%, more preferably 16.6%, more preferably 16.4%, more preferably 16.2%, and most preferably 16%.
[0029] B2O3 is a component that improves solubility and resistance to devitrification. If the content of B2O3 is too little, the solubility and resistance to devitrification are easily reduced. Therefore, the lower limit of B2O3 is preferably 0%, more preferably more than 0%, more preferably 0.1%, further preferably 0.2%, further preferably 0.3%, further preferably 0.4%, and most preferably more than 1%. On the other hand, if the content of B2O3 is too much, Young's modulus and strain point are easily reduced. Therefore, the upper limit of B2O3 is preferably 5%, more preferably 4.8%, more preferably 4.6%, further preferably 4.4%, further preferably 4.2%, and most preferably 4%.
[0030] Li2O, Na2O and K2O are components inevitably mixed from glass raw materials, and their total amount is preferably 0 to 0.5%, more preferably 0 to 0.3%, and most preferably 0 to 0.2%. If the total amount of Li2O, Na2O and K2O is too much, there is a possibility that alkali ions will diffuse into the semiconductor material after film formation during the heat treatment process.
[0031] MgO is a component that significantly improves Young's modulus in alkaline earth metal oxides. If the content of MgO is too little, the solubility and Young's modulus are easily reduced. Therefore, the lower limit of MgO is preferably 5%, more preferably 5.1%, more preferably 5.2%, further preferably 5.3%, further preferably 5.4%, further preferably 5.5%, further preferably 5.6%, and most preferably 5.7%. On the other hand, if the content of MgO is too much, devitrified crystals such as mullite become easy to precipitate, and the liquidus viscosity is easy to reduce. Therefore, the upper limit of MgO is preferably 9%, more preferably 8.9%, more preferably 8.8%, further preferably 8.7%, further preferably 8.6%, further preferably 8.5%, further preferably less than 8.5%, further preferably 8.4%, and most preferably less than 8.4%.
[0032] CaO is a component that reduces high temperature viscosity and significantly improves solubility without reducing the strain point. It is also a component that increases Young's modulus. If the content of CaO is too little, it is difficult to enjoy the above-mentioned effects, and the solubility is easily reduced. And then the resistance to devitrification is easily reduced. Therefore, the lower limit of CaO is preferably 2%, more preferably 2.2%, more preferably 2.4%, more preferably 2.5%, more preferably 2.6%, more preferably 2.8%, more preferably 3%, and most preferably more than 3%. On the other hand, if the content of CaO is too much, the liquidus temperature becomes high. Therefore, the upper limit of CaO is preferably 10%, more preferably 9.9%, more preferably 9.8%, more preferably 9.7%, more preferably 9.6%, more preferably 9.5%, more preferably 9.4%, more preferably 9.3%, and most preferably 9.2%.
[0033] SrO is a component that improves resistance to devitrification, and a component that reduces high-temperature viscosity and improves solubility without reducing the strain point. It is also a component that suppresses the reduction of liquidus viscosity. If the content of SrO is too little, it is difficult to enjoy the above-mentioned effect. Therefore, the lower limit of SrO is preferably 0%, more preferably more than 0%, more preferably 0.1%, more preferably more than 0.1%, more preferably 0.2%, more preferably 0.3%, more preferably more than 0.3%, more preferably 0.4%, and most preferably more than 0.4%. On the other hand, if the content of SrO is too much, the thermal expansion coefficient and density are likely to increase. Therefore, the upper limit of SrO is preferably 6%, more preferably less than 6%, more preferably 5.9%, more preferably less than 5.9%, more preferably 5.8%, more preferably less than 5.8%, more preferably 5.7%, more preferably less than 5%, more preferably 4%, and most preferably 3%.
[0034] BaO is a component that improves resistance to devitrification. If the content of BaO is too little, it is difficult to enjoy the above effect. Therefore, the lower limit of BaO is preferably more than 1%, more preferably 1.1%, more preferably 1.2%, more preferably 1.3%, more preferably 1.4%, more preferably 1.5%, more preferably 1.6%, and most preferably 1.7%. On the other hand, if the content of BaO is too much, Young's modulus is easily reduced, and the thermal expansion coefficient and density are easily increased. Therefore, the upper limit of BaO is preferably 7%, more preferably 6.8%, more preferably 6.6%, more preferably 6.4%, more preferably 6.2%, more preferably 6%, and most preferably less than 6%.
[0035] The total amount of MgO, CaO, SrO and BaO is too much or too little, and the solubility is easy to deteriorate. If the total amount of MgO, CaO, SrO and BaO is too little, the solubility is easy to reduce, and the Young's modulus is also easy to reduce. Therefore, the lower limit of the total amount of MgO, CaO, SrO and BaO is preferably 14%, more preferably 14.5%, more preferably 15%, more preferably 15.3%, more preferably 15.5%, more preferably 15.8%, more preferably 15.9%, and most preferably 16%. On the other hand, if the total amount of MgO, CaO, SrO and BaO is too much, the thermal expansion coefficient and density are easy to increase. Therefore, the upper limit of the total amount of MgO, CaO, SrO and BaO is preferably 20%, more preferably 19.8%, more preferably 19.6%, more preferably 19.4%, more preferably 19.2%, more preferably 19%, and most preferably less than 19%.
[0036] If the mol ratio Al2O3 / BaO is too small, the Young's modulus is easily reduced. Therefore, the lower limit of Al2O3 / BaO is preferably 1.8, more preferably 2, more preferably 3, further preferably 4, further preferably 4.5, and most preferably 5. If Al2O3 / BaO is too large, the liquidus viscosity is easily reduced. Therefore, the upper limit of Al2O3 / BaO is preferably 10, more preferably 9.8, more preferably 9.6, further preferably 9.4, further preferably 9.2, and most preferably 9.
[0037] If the mol ratio B2O3 / (MgO+CaO+SrO+BaO) is too small, the solubility is likely to decrease. Therefore, the lower limit of B2O3 / (MgO+CaO+SrO+BaO) is preferably 0, more preferably greater than 0, more preferably 0.01, further preferably 0.02, further preferably 0.03, and most preferably 0.04. If B2O3 / (MgO+CaO+SrO+BaO) is too large, the strain point is likely to decrease. Therefore, the upper limit of B2O3 / (MgO+CaO+SrO+BaO) is preferably 0.2, more preferably 0.19, more preferably 0.18, further preferably 0.17, further preferably 0.16, and most preferably 0.15.
[0038] If the molar ratio (B2O3+MgO) / SiO2 is too small, the solubility is easily reduced. Therefore, the lower limit of (B2O3+MgO) / SiO2 is preferably 0.1, more preferably more than 0.1, more preferably 0.11, further preferably 0.12, further preferably 0.13, and most preferably 0.14. If (B2O3+MgO) / SiO2 is too large, the strain point is easily reduced. Therefore, the upper limit of (B2O3+MgO) / SiO2 is preferably 0.2, more preferably less than 0.2, more preferably 0.19, further preferably 0.18, further preferably 0.17, and most preferably 0.16.
[0039] The mol ratio B2O3 / MgO is an important component ratio for achieving both high Young's modulus and high solubility, low thermal shrinkage, and productivity. If B2O3 / MgO is too small, the liquidus temperature becomes high and productivity decreases, or solubility is easily reduced, or the forming temperature becomes high, the life of the formed body becomes short, and the cost of the glass increases. Therefore, the lower limit of B2O3 / MgO is preferably 0, more preferably greater than 0, more preferably 0.03, further preferably 0.05, further preferably 0.08, and most preferably 0.1. If B2O3 / MgO is too large, the strain point decreases, high thermal dimensional stability cannot be obtained, or the Young's modulus decreases, and large glass plates become easy to bend. Therefore, the upper limit of B2O3 / MgO is preferably 0.5, more preferably 0.48, more preferably 0.46, further preferably 0.44, further preferably 0.42, further preferably 0.40, further preferably 0.37, further preferably 0.36, further preferably 0.35, further preferably 0.33, and most preferably 0.30.
[0040] In addition to the above components, for example, the following components may be added as optional components. In order to reliably obtain the effects of the present invention, the total content of the components other than the above components is preferably 10% or less, particularly 5% or less.
[0041] P2O5 is a component that increases the strain point and is also a component that can significantly inhibit the precipitation of devitrified crystals of alkaline earth aluminosilicates such as calcium feldspar. However, if a large amount of P2O5 is contained, the glass becomes prone to phase separation. The content of P2O5 is preferably 0 to 2.5%, more preferably 0.0005 to 1.5%, further preferably 0.001 to 0.5%, and particularly preferably 0.005 to 0.3%.
[0042] TiO2 is a component that reduces high temperature viscosity, improves melting properties, and inhibits exposure to sunlight. However, if a large amount of TiO2 is contained, the glass will be colored and the transmittance will be easily reduced. The content of TiO2 is preferably 0 to 2.5%, more preferably 0.0005 to 1%, further preferably 0.001 to 0.5%, and particularly preferably 0.005 to 0.1%.
[0043] ZnO is a component that improves melting properties. However, if a large amount of ZnO is contained, the glass is prone to devitrification and the strain point is prone to decrease. The ZnO content is preferably 0-6%, 0-5%, 0-4%, and particularly 0% or more and less than 3%.
[0044] Y2O3, Nb2O5, and La2O3 have the effect of increasing the strain point, Young's modulus, etc. The total amount and the content of each of these components are preferably 0 to 5%, more preferably 0 to 1%, and further preferably 0 to 0.5%. If the total amount and the content of each of Y2O3, Nb2O5, and La2O3 are too much, the density and the raw material cost are likely to increase.
[0045] SnO2 is a component that has a good clarification effect in the high temperature domain, and is also a component that increases the strain point and reduces the high temperature viscosity. The content of SnO2 is preferably 0-1%, 0.001-1%, 0.01-0.5%, and particularly 0.05-0.3%. If the content of SnO2 is too much, devitrified crystals of SnO2 are easily precipitated. It should be noted that if the content of SnO2 is less than 0.001%, it is difficult to enjoy the above-mentioned effects.
[0046] As mentioned above, SnO2 is suitable as a clarifier, but as long as the glass properties are not impaired, F, SO3, C or metal powders such as Al and Si can be added as a clarifier in place of SnO2 or together with SnO2 to 5% (preferably 1%, especially 0.5%) respectively. In addition, CeO2 etc. can also be added as a clarifier to 5% (preferably 1%, especially 0.5%).
[0047] As clarifiers, As2O3 and Sb2O3 are also effective. However, from the perspective of the environment, the alkali-free glass plate of the present invention does not substantially contain these components. If As2O3 is still contained, the resistance to solar radiation tends to decrease.
[0048] Cl is a component that promotes the initial melting of glass batch. In addition, if Cl is added, the effect of the clarifier can be promoted. As a result, the melting cost can be reduced and the life of the glass manufacturing kiln can be extended. However, if the Cl content is too much, the strain point is easily reduced. Therefore, the Cl content is preferably 0 to 3%, more preferably 0.0005 to 1%, and particularly preferably 0.001 to 0.5%. It should be noted that as the raw material for introducing Cl, chlorides of alkaline earth metal oxides such as strontium chloride or raw materials such as aluminum chloride can be used.
[0049] Fe2O3 is a component mixed as a raw material impurity, and is a component that reduces resistivity. The content of Fe2O3 is preferably 0 to 300 mass ppm, 80 to 250 mass ppm, and particularly 100 to 200 mass ppm. If the content of Fe2O3 is too little, the cost of raw materials tends to rise. On the other hand, if the content of Fe2O3 is too much, the resistivity of the molten glass increases, making it difficult to perform electric melting.
[0050] Particularly preferably, the glass composition range contains SiO2 65-70%, Al2O3 12.5-16%, B2O3 0-4%, Li2O+Na2O+K2O 0-0.5%, MgO 5.7-9%, CaO 3-10%, SrO 0-6%, BaO more than 1% and less than 6%, MgO+CaO+SrO+BaO 16-19%, mol ratio Al2O3 / BaO 2-9, mol ratio B2O3 / (MgO+CaO+SrO+BaO) 0-0.15, mol ratio (B2O3+MgO) / SiO2 0.1-0.2, and mol ratio B2O3 / MgO 0.1-0.36. Thus, a high Young's modulus, a high strain point, and high heat resistance (high thermal dimensional stability) can be ensured, and productivity can be improved.
[0051] The alkali-free glass plate of the present invention preferably has the following properties.
[0052] The average thermal expansion coefficient in the temperature range of 30 to 380°C is preferably 30×10 -7 ~50×10 -7 / ℃、32×10 -7 ~48×10 -7 / ℃、33×10 -7 ~45×10 -7 / ℃、34×10 -7 ~44×10 -7 / ℃, especially 35×10 -7 ~43×10 -7 / °C. This makes it easy to match the thermal expansion coefficient with that of Si used in TFTs.
[0053] The Young's modulus is 80 GPa or more, preferably more than 80 GPa, more than 81 GPa, more than 81 GPa, more than 82 GPa, more than 83 GPa, more than 84 GPa, and particularly more than 84 GPa and less than 95 GPa. If the Young's modulus is too low, defects caused by deflection of the glass plate are likely to occur.
[0054] The strain point is 700° C. or higher, preferably more than 700° C. and 705° C. or higher, and particularly 710 to 770° C. In this way, heat shrinkage of the glass sheet can be suppressed in the LTPS process.
[0055] The liquidus temperature is below 1350°C, preferably below 1350°C and below 1300°C, and particularly 800 to 1280°C. In this way, it is easy to prevent the occurrence of devitrification crystallization during glass manufacturing and the reduction of productivity. In addition, since it is easy to form using the overflow down-draw method, it is easy to improve the surface quality of the glass sheet and the manufacturing cost of the glass sheet can be reduced. It should be noted that the liquidus temperature is an indicator of devitrification resistance, and the lower the liquidus temperature, the better the devitrification resistance.
[0056] The liquid phase viscosity is preferably 10 4.0 dPa·s or more, 10 4.1 dPa·s or more, 10 4.2 dPa·s or more, especially 10 4.3 dPa·s or more. In this way, devitrification is not likely to occur during forming, so it is easy to form using the overflow down-draw method, resulting in improved surface quality of the glass sheet and reduced manufacturing cost of the glass sheet. It should be noted that liquidus viscosity is an indicator of devitrification resistance and formability, and the higher the liquidus viscosity, the higher the devitrification resistance and formability.
[0057] High temperature viscosity 10 2.5 The temperature at dPa·s is preferably 1650°C or less, 1630°C or less, 1610°C or less, and particularly 1600°C or less. 2.5 dPa·s, the glass batch material becomes difficult to melt, and the production cost of the glass plate increases. 2.5 The temperature in dPa·s corresponds to the melting temperature, and the lower the temperature is, the higher the meltability is.
[0058] β-OH is an indicator of the water content in the glass. If β-OH is reduced, the strain point can be increased. In addition, when the glass composition is the same, the thermal shrinkage rate at a temperature below the strain point becomes smaller when β-OH is small. β-OH is preferably below 0.35 / mm, below 0.30 / mm, below 0.28 / mm, below 0.25 / mm, and especially below 0.20 / mm. It should be noted that if β-OH is too small, the solubility is easily reduced. Therefore, β-OH is preferably above 0.01 / mm, especially above 0.03 / mm.
[0059] The following methods can be cited as methods for reducing β-OH. (1) Selecting raw materials with low water content. (2) Adding components that reduce β-OH (Cl, SO3, etc.) to the glass. (3) Reducing the water content in the furnace atmosphere. (4) Bubbling N2 in the molten glass. (5) Using a small melting furnace. (6) Increasing the flow rate of molten glass. (7) Using electric melting.
[0060] Here, "β-OH" refers to a value obtained by measuring the transmittance of glass by FT-IR and using the following Mathematical Formula 1.
[0061]
Mathematical formula 1
[0062] β-OH=(1 / X)log(T1 / T2)
[0063] X: Plate thickness (mm)
[0064] T1: Reference wavelength 3846cm -1 Transmittance under (%)
[0065] T2: Hydroxyl absorption wavelength 3600cm -1 Minimum transmittance near (%)
[0066] The alkali-free glass sheet of the present invention is preferably formed by an overflow down-draw method. The overflow down-draw method is a method of manufacturing a glass sheet by causing molten glass to overflow from both sides of a heat-resistant trough-shaped structure, while causing the overflowed molten glass to merge at the lower end of the trough-shaped structure and stretching the glass sheet downward. In the overflow down-draw method, the surface that will become the surface of the glass sheet does not contact the trough-shaped refractory material, and is formed in a free surface state. Therefore, it is possible to manufacture a glass sheet that is not ground and has good surface quality at a low cost, and it is also easy to make it thin.
[0067] In addition to the overflow down-draw method, a glass sheet can be formed by, for example, a down-draw method (such as a slot down-draw method) or a float method.
[0068] In the alkali-free glass plate of the present invention, the plate thickness is not particularly limited, but is preferably less than 0.7 mm, less than 0.6 mm, less than 0.6 mm, and particularly less than 0.5 mm. The thinner the plate thickness, the lighter the organic EL device can be. The plate thickness can be adjusted by the flow rate, plate pulling speed, etc. during glass manufacturing.
[0069] The alkali-free glass plate of the present invention is preferably used for organic EL devices, especially substrates of display panels for organic EL televisions and carriers for manufacturing organic EL display panels. In the use of organic EL televisions, after a plurality of devices are manufactured on a glass plate, each device is divided and cut to achieve cost reduction (so-called panel assembly). The alkali-free glass plate of the present invention has a low liquidus temperature and a high liquidus viscosity, so it is easy to form a large glass plate, and can reliably meet such requirements.
[0070] Example
[0071] Hereinafter, the present invention will be described based on examples. It should be noted that the following examples are only for illustration and the present invention is not limited to the following examples in any way.
[0072] Table 1 shows examples of the present invention (samples No. 1 to 12). It should be noted that RO in the table represents MgO+CaO+SrO+BaO. Although not explicitly shown in the table, Na2O is mixed in the glass composition at about 0.005 to 0.02 mol% as an inevitable impurity derived from glass raw materials.
[0073]
Table 1
[0074]
[0075] First, a glass batch prepared with glass raw materials in the manner of the glass composition in the table was placed in a platinum crucible and melted at 1600-1650°C for 24 hours. When the glass batch was melted, it was stirred with a platinum stirrer for homogenization. Next, the molten glass was poured onto a carbon plate, formed into a plate, and then annealed at a temperature near the annealing point for 30 minutes. For each sample obtained, the average thermal expansion coefficient CTE in the temperature range of 30-380°C, density, Young's modulus, strain point Ps, annealing point Ta, softening point Ts, high temperature viscosity 10 4 Temperature at dPa·s, high temperature viscosity 10 3 Temperature at dPa·s, high temperature viscosity 10 2.5 Temperature at dPa·s, liquidus temperature TL, and viscosity log at liquidus temperature TL 10 ηTL.
[0076] The average thermal expansion coefficient CTE in the temperature range of 30 to 380° C. is a value measured using a dilatometer.
[0077] The density is a value measured by the known Archimedean method.
[0078] The Young's modulus is a value measured by a known resonance method.
[0079] The strain point Ps, annealing point Ta, and softening point Ts are values measured according to the methods of ASTM C336 and C338.
[0080] High temperature viscosity 10 4 dPa·s, 10 3 dPa·s, 10 2.5 The temperature in dPa·s is a value measured by a platinum ball pulling method.
[0081] The liquidus temperature TL is the temperature at which crystals are precipitated when glass powder that passes through a standard sieve of 30 mesh (500 μm) and remains in a sieve of 50 mesh (300 μm) is placed in a platinum boat and kept in a temperature gradient furnace for 24 hours.
[0082] Liquid viscosity log 10 ηTL is a value obtained by measuring the viscosity of glass at the liquidus temperature TL using a platinum ball pulling method.
[0083] As can be seen from Table 1, Samples No. 1 to 12 do not contain alkali metal oxides in the glass composition, have a Young's modulus of 84 GPa or more, a strain point of 740°C or more, and a liquidus temperature of 1285°C or less, so they have good productivity, can reduce thermal shrinkage in the LTPS process, and are considered unlikely to have defects due to bending even if they are enlarged or thinned. Therefore, Samples No. 1 to 12 are suitable for substrates of organic EL devices.
[0084] Industrial Applicability
[0085] The alkali-free glass plate of the present invention is suitable as a substrate for an organic EL device, in particular, a display panel for an organic EL television, a carrier for manufacturing an organic EL display panel, and is also suitable as a substrate for a flat-panel display such as a liquid crystal display, a glass substrate for a magnetic recording medium, a cover glass for an image sensor such as a charge coupled device (CCD) and a close proximity type solid-state imaging element (CIS), a substrate and cover glass for a solar cell, a substrate for organic EL lighting, and the like.
Claims
1. An alkali-free glass plate, characterized in that: The glass composition contains, in mol%, 64% to 71% SiO2, 13% to 17% Al2O3, 0% to 5% B2O3, 0% to 0.5% Li2O + Na2O + K2O, 5% to 9% MgO, 4% to 10% CaO, 0% to 7% SrO, more than 1% and less than 7% BaO, 14% to 20% MgO + CaO + SrO + BaO, the mol ratio Al2O3 / BaO is 1.8 to 10, the mol ratio B2O3 / (MgO + CaO + SrO + BaO) is 0 to 0.2, the mol ratio (B2O3 + MgO) / SiO2 is 0.1 to 0.15, the mol ratio B2O3 / MgO is 0 to 0.5, the Young's modulus is not less than 83 GPa, the strain point is not less than 740°C, and the liquidus temperature is not more than 1350°C.
2. The alkali-free glass plate according to claim 1, characterized in that It also contains substantially no As2O3 and Sb2O3.
3. The alkali-free glass plate according to claim 1 or 2, characterized in that: It also contains 0.001 mol% to 1 mol% of SnO2.
4. The alkali-free glass plate according to claim 1 or 2, characterized in that: The average thermal expansion coefficient in the temperature range of 30℃~380℃ is 30×10 -7 / ℃~50×10 -7 / ℃.
5. The alkali-free glass plate according to claim 1 or 2, characterized in that: Liquid viscosity is 10 4.0 dPa·s or above.
6. The alkali-free glass plate according to claim 1 or 2, characterized in that: Used in organic EL devices.
Citation Information
Patent Citations
Alkali-free glass
JP2012106919A
Non-alkali glass
CN103313948A
Glass substrate for liquid crystal lens
CN103492333A
Non-alkali glass substrate
CN104854050A
Alkali-free glass
US20120282450A1